Neglected Avian Blood Parasites (Onchocercidae and Trypanosomatidae) in Migratory Passerines of the Temperate Zone, Eastern Baltic Region - Rasa Bernotienė; Tatjana Iezhova; Vytautas Eigirdas; Vytautas Jusys; Margarita Kazak; Rasa Binkienė (Pathogens)
Passerine birds (n = 3335) of 19 species were caught and investigated for the presence of Trypanosomatidae and Onchocercidae parasites using the buffy coat method, microscopy and PCR in Ventės Ragas, Lithuania. Data on the spread patterns of these parasites are still lacking. The prevalences of Trypanosoma parasites in birds of different species varied from 2.2% to 36.1%, while the prevalences of Onchocercidae parasites varied from 0% to 17.3%. Statistically significant differences between spring and autumn in the prevalences of Trypanosomatidae were determined for Acrocephalus schoenobaenus, Hirundo rustica and Turdus philomelos. No significant differences between the prevalences of Onchocercidae in spring and autumn were determined. The prevalence of Trypanosoma was significantly higher for long-distance migrant birds compared with short-distance migrants, for omnivorous birds compared with insectivorous birds, and for open-nesting birds compared with birds nesting in nest boxes. The prevalences of Onchocercidae parasites did not differ for the same bird groups except for the prevalence in omnivorous birds, which was higher compared with insectivorous birds. Both groups of parasites were detected in juveniles, showing the presence of transmission in the study area. The diet, breeding behaviour and migration features of avian hosts can influence the prevalence of avian blood parasites.